2021
DOI: 10.1097/wno.0000000000001421
|View full text |Cite
|
Sign up to set email alerts
|

Ophthalmological Evaluation in Children Presenting With a Primary Brain Tumor

Abstract: Background: Children with a brain tumor are prone to develop visual impairment, which to date is often underestimated and unrecognized. Our aim was to assess the prevalence of ophthalmological evaluation and abnormal ophthalmological findings, and investigate whether demographic and tumor-related characteristics are associated with abnormal ophthalmological findings in children presenting with a primary brain tumor. Methods: Medical records of all 90 children diagnosed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
13
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 53 publications
0
13
1
Order By: Relevance
“…A study by Nuijts et al examining the ophthalmological findings in children presenting with primary brain tumors found that papilledema was present in nearly half (44.1%) of patients. 8 In our study, tumors represented only 1.9% of our overall population and 6.3% of the patients with papilledema; conversely, all 4 patients with intracranial tumors presented with papilledema. Our overall prevalence was also lower than the 15.8% of children with papilledema who were diagnosed with tumors in a study by Hyde et.…”
Section: Discussioncontrasting
confidence: 53%
“…A study by Nuijts et al examining the ophthalmological findings in children presenting with primary brain tumors found that papilledema was present in nearly half (44.1%) of patients. 8 In our study, tumors represented only 1.9% of our overall population and 6.3% of the patients with papilledema; conversely, all 4 patients with intracranial tumors presented with papilledema. Our overall prevalence was also lower than the 15.8% of children with papilledema who were diagnosed with tumors in a study by Hyde et.…”
Section: Discussioncontrasting
confidence: 53%
“…These findings are in line with previous studies, although the exact prevalence numbers of the specific ophthalmological diagnoses slightly differ. In particular, the percentage of papilledema was higher (74%) 34 and lower (11%-44%) 12,13,19,[35][36][37] in previous studies, whereas the percentage of visual field defects was comparable (27%) 13 or higher (50%-58%) 12,34 in previous studies, and the percentage of decreased VA (50%-54%) 13,20 and strabismus (45%-60%) 12,13,19,20 was higher in previous studies. An explanation for these differences in prevalence numbers may be referral and selection bias in previous retrospective studies, as also suggested by some of the authors 12,13,19,20 ; these biases are feasible given the incomplete ophthalmological evaluation in a substantial proportion of the included children in those studies.…”
Section: Discussionmentioning
confidence: 85%
“…In particular, the percentage of papilledema was higher (74%) 34 and lower (11%-44%) 12,13,19,[35][36][37] in previous studies, whereas the percentage of visual field defects was comparable (27%) 13 or higher (50%-58%) 12,34 in previous studies, and the percentage of decreased VA (50%-54%) 13,20 and strabismus (45%-60%) 12,13,19,20 was higher in previous studies. An explanation for these differences in prevalence numbers may be referral and selection bias in previous retrospective studies, as also suggested by some of the authors 12,13,19,20 ; these biases are feasible given the incomplete ophthalmological evaluation in a substantial proportion of the included children in those studies. One study 20 only reported ophthalmological findings for children who initially presented to the ophthalmologist, which may explain the higher prevalence of abnormal ophthalmological findings in that study.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations